Elégiák az 1945 utáni angol költészetben - D. Rácz, István (Studia Litteraria, 2016)
As has frequently been remarked in poetry criticism, an elegy always suggests that the poet’s own death is inconceivable. What I add is that in many cases the lost person’s death is also inconceivable or, at least, unspeakable; therefore, the poet has to turn to something speakable, meaning repeatable: a form, a motif, etc. This means that there is always something in the poem that admittedly does not belong to the author’s subjectivity. In my study I offer a survey of three British poets’ elegies from the second half of the 20th century: sequences by Douglas Dunn, Peter Porter and Thom Gunn; the former two writing to commemorate their dead wives, and Gunn writing in memory of his lost friends. As I argue, all the three poets follow in the wake of classic examples to repeat and reiterate something that belongs to tradition: Dunn is inspired by the classic dramatic monologue and gaps in medieval ballads, Porter by Henry King’s poem, and Gunn by romantic poetry. All the three can be read as self-elegies: Dunn’s poems through the motif of the wedding rings, Porter’s through the motif of the dead wife waiting for him, and Gunn’s through the image of the dream where the two friends are united. Probably all elegies can be read as self-elegies, signifying that we speak about someone else’s death because we are unable to speak of our own.